2014
DOI: 10.1111/ppa.12267
|View full text |Cite
|
Sign up to set email alerts
|

Pyramiding Ty‐2 and Ty‐3 genes for resistance to monopartite and bipartite tomato leaf curl viruses of India

Abstract: Breeding resistance to whitefly‐transmitted begomoviruses is an important goal of tomato breeding programmes worldwide. So far, resistance to begomoviruses in tomato has been achieved using wild species, and at least five resistance genes (Ty genes) have been studied. The present study was undertaken to combine Ty‐2 and Ty‐3 and to determine the effect of pyramiding on infection of tomato by three diverse begomovirus species. The diagnostic ability of the markers linked to Ty genes was assessed and marker‐assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 33 publications
2
63
0
Order By: Relevance
“…Nevertheless, if efficient spread to tomato occurs, here we showed that the Ty-1 gene already deployed for the control TYLCD-associated viruses [49] seems to provide resistance to ToLCNDV, even for the isolate from India that causes severe infections in susceptible tomatoes. Moreover, other gene combinations have been reported to provide effective resistance to ToLCNDV infections in tomato [50,51]. …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, if efficient spread to tomato occurs, here we showed that the Ty-1 gene already deployed for the control TYLCD-associated viruses [49] seems to provide resistance to ToLCNDV, even for the isolate from India that causes severe infections in susceptible tomatoes. Moreover, other gene combinations have been reported to provide effective resistance to ToLCNDV infections in tomato [50,51]. …”
Section: Discussionmentioning
confidence: 99%
“…Unlike Rx-mediated resistance that results in extreme resistance (ER) against potato virus X [110], TYLCV mediated resistance results in virus tolerance rather than immunity. Functional Ty-1/Ty-3-like alleles are also present in several other S. chilense wild type tomato accessions, shown by fine mapping and VIGS [111]. Additionally, the DFDGD catalytic domain of the Ty-1and Ty-3 genes is conserved among Solanum species [111].…”
Section: Virusesmentioning
confidence: 88%
“…Functional Ty-1/Ty-3-like alleles are also present in several other S. chilense wild type tomato accessions, shown by fine mapping and VIGS [111]. Additionally, the DFDGD catalytic domain of the Ty-1and Ty-3 genes is conserved among Solanum species [111]. In a recent study, Ty-2 and Ty-3 genes were used to develop a series of R-gene pyramided tomato lines and the linked markers were evaluated for their diagnostic value and utility in pyramiding Ty genes [112].…”
mentioning
confidence: 99%
“…Another option to reduce or eliminate the negative effect of the Ty-1 gene introgression in homozygous state could be the introduction of others genes, as the Ty-2 gene, derived from Solanum habrochaitesderived line H24 (Hanson et al, 2000), the Ty-3 gene (allelic to Ty-1), derived from S. chilense accessions LA2779 and LA1932 (Verlaan et al, 2013), the Ty-4 gene, derived from S. chilense (Ji et al, 2009) or the Ty-5 gene, derived from the cultivar Tyking (Hutton et al, 2012). Recently, Prasanna et al (2015) reported that the Ty-2 and Ty-3 gene pyramiding produces tomato lines with a high level of resistance to the begomoviruses tested, achieving broad-spectrum resistance.…”
Section: Discussionmentioning
confidence: 98%